Gondolatok Paul Krugman 2008 évi Nobel-díjas amerikai közgazdász munkásságáról - Veres, Lajos; Abonyiné Palotás, Jolán (Közép-Európai Közlemények, 2009)
Paul Krugman, the American economist was awarded the Nobel Prize in economics in 2008. Krugman, by setting up new laws on the recognition of new correlations and by placing the theories related to previous trade on new grounds, demonstrated the strengthening of the centralisation process caused by globalisation, drew our attention to the regions and recognised the topical issues of contemporary economic geography reacting to the rapid processes of the world economy. He warned us in due time of the danger of the unfurling financial crisis, welcomed the fast reactions of some governments and criticised the unfounded measures. He was quick to react to the current economic and financial situation of our world. After the award ceremony he said in the Swedish television that he wished to continue his research career and hoped that “his life would not be thoroughly changed by the award”.